Corporate Responsibility Strategy as a Growth Factor for Companies Ningbo Xinle Electric Appliance Co., Ltd - Bingjie Jin; Aleksandr Koberidze (Communications of International Proceedings, 2021)
The object of the research is to consider the main theories related to the instrumental approach to corporate social responsibility, according to which socially responsible behavior of companies is perceived as a mechanism for achieving the growth of the enterprise in the long term by increasing the loyal attitude of various groups of stakeholders and the perception of the company as reliable by market participants. The paper provides information on foreign and domestic studies that empirically confirm the existence of a positive relationship between the level of corporate social responsibility and the financial efficiency of organizations.
Keywords: Strategies; Behavior; Corporate Responsibility; Growth Factor; Financial Performance.